2008
DOI: 10.4161/cbt.7.8.6215
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for mitochondria in regulating epigenetic modifications in the nucleus

Abstract: Epigenetic modification in the nuclear genome plays a key role in human tumorigenesis. In this paper, we investigated whether changes in the mtDNA copy number frequently reported to vary in a number of human tumors induce methylation changes in the nucleus. We utilized the Restriction Landmark Genomic Scanning (RLGS) to identify genes that undergo changes in their methylation status in response to the depletion and repletion of mtDNA. Our study demonstrates that depletion of mtDNA results in significant change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(117 citation statements)
references
References 59 publications
1
116
0
Order By: Relevance
“…One of the regions looked at further in this study was the aberrant promoter methylation of the BC030713 mRNA transcript that had been previously identified using RLGS. 5,85 The study showed that the 5' UTR comprising a CpG island was partially hypo/unmethylated in 143B rho 0 compared with the parental cell line that was completely hypermethylated at this region. The study concluded that this partial loss of genomic DNA methylation could be associated with the loss of mitochondrial DNA (mtDNA) and the mitochondria itself; 5 however, it does not disqualify a perturbed genome-wide methylation profile.…”
Section: A Role For "Mitocheckpoint" In Pathogenesis Of Human Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the regions looked at further in this study was the aberrant promoter methylation of the BC030713 mRNA transcript that had been previously identified using RLGS. 5,85 The study showed that the 5' UTR comprising a CpG island was partially hypo/unmethylated in 143B rho 0 compared with the parental cell line that was completely hypermethylated at this region. The study concluded that this partial loss of genomic DNA methylation could be associated with the loss of mitochondrial DNA (mtDNA) and the mitochondria itself; 5 however, it does not disqualify a perturbed genome-wide methylation profile.…”
Section: A Role For "Mitocheckpoint" In Pathogenesis Of Human Diseasesmentioning
confidence: 99%
“…5,33,34 Epigenetic modifications are known to regulate gene expression either in a permanent or transient manner. 35 These epigenetic mechanisms that alter the rate of gene expression without actually changing the physical sequence of nuclear encoded genomic DNA are categorized into three broad groups.…”
Section: The Mammalian Nuclear and Mitochondrial Epigenomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The close proximity of mtDNA to the ROS production site makes this genome vulnerable to oxidative damage. Mitochondrial dysfunction and associated mtDNA depletion possibly reversibly control epigenetic changes in the nucleus that contributes to cancer development (1). Thus, targeting mtDNA could lead to novel and effective therapies for aggressive cancers.…”
mentioning
confidence: 99%
“…No information regarding the submitochondrial localization of ANT3 and ANT4 are available to date. In addition, differences in the epigenetic modification of ANT isoformes in cancer could help to better understand the differential roles of the isoforms as discussed for other mitochondrial proteins (Smiraglia et al, 2008). Hence, a complete elucidation of the complex interplay of the various ANT isoforms in cancer cells might have crucial implications for a better understanding of the bioenergetic metabolism of cancer cells and the design of novel mitochondrial-targeted anticancer therapies (Fulda et al, 2010).…”
Section: Open Questions and Perspectivesmentioning
confidence: 99%